Exacerbations of severe asthma: a focus on steroid therapy - Spaggiari, Lorenza; Bertorelli, Giuseppina; Ridolo, Erminia; Morelli, Ilaria; Guida, Loredana; Pigna, Federica; Ticinesi, Andrea; Nouvenne, Antonio; Borghi, Loris; Meschi, Tiziana (Acta Biomedica Atenei Parmensis, 2014)
Bronchial asthma remains one of the most common chronic diseases in the world; approximately 10% of patients shows exacerbations severe enough to be judged life-threatening, whereas around 2-20% of patients are admitted to the Intensive Care Unit (ICU). Acute severe asthma is a dangerous condition where the deterioration of the asthmatic exacerbation usually progresses over days or weeks, although in a few patients over hours or even minutes. Morbidity and mortality are mainly related to the underestimation of the severity of the exacerbation, delay in referring to hospital and inadequate emergency treatment. The cornerstone measures of therapy for acute severe asthma are oxygen supplementation, as to achieve arterial saturation >90%, and repetitive or continuous administration of bronchodilators (short-acting inhaled β2-agonists and ipratropium bromide) and corticosteroids. Despite extensive clinical experience in treatment of chronic asthma with steroids, there is considerable uncertainty about the accurate use of these agents for treatment of acute severe asthma in emergency settings.